Exercise Training Reduces Peripheral Arterial Stiffness and Myocardial Oxygen Demand in Young Prehypertensive Subjects - Beck, Darren T.; Martin, Jeffrey S.; Casey, Darren P.; Braith, Randy W. (American journal of hypertension, 2013)
BACKGROUND Large artery stiffness is a major risk factor for the development of hypertension and cardiovascular disease. Persistent prehypertension accelerates the progression of arterial stiffness. METHODS Forty-three unmedicated prehypertensive (systolic blood pressure (SBP) = 120-139mm Hg or diastolic blood pressure (DBP) = 80-89mm Hg) men and women and 15 normotensive time-matched control subjects (NMTCs; n = 15) aged 18-35 years of age met screening requirements and participated in the study. Prehypertensive subjects were randomly assigned to a resistance exercise training (PHRT; n = 15), endurance exercise training (PHET; n = 13) or time-control group (PHTC; n = 15). Treatment groups performed exercise training 3 days per week for 8 weeks. Pulse wave analysis, pulse wave velocity (PWV), and central and peripheral blood pressures were evaluated before and after exercise intervention or time-matched control. RESULTS PHRT and PHET reduced resting SBP by 9.6±3.6mm Hg and 11.9±3.4mm Hg, respectively, and DBP by 8.0±5.1mm Hg and 7.2±3.4mm Hg, respectively (P < 0.05). PHRT and PHET decreased augmentation index (AIx) by 7.5% ± 2.8% and 8.1% ± 3.2% (P < 0.05), AIx@75 by 8.0% ± 3.2% and 9.2% ± 3.8% (P < 0.05), and left ventricular wasted pressure energy, an index of extra left ventricular myocardial oxygen requirement due to early systolic wave reflection, by 573±161 dynes s/cm2 and 612±167 dynes s/cm2 (P < 0.05), respectively. PHRT and PHET reduced carotid-radial PWV by 1.02±0.32 m/sec and 0.92±0.36 m/sec (P < 0.05) and femoral-distal PWV by 1.04±0.31 m/sec and 1.34±0.33 m/sec (P < 0.05), respectively. No significant changes were observed in the time-control groups. CONCLUSIONS This study suggests that both resistance and endurance exercise alone effectively reduce peripheral arterial stiffness, central blood pressures, augmentation index, and myocardial oxygen demand in young prehypertensive subjects.